Osteoporosis – a frequent problem of postmenopausal woman - Suzin, Jacek; Szubert, Maria; Kowalczyk-Amico, Katarzyna (Menopause Review/Przegląd Menopauzalny, 2009)
Osteoporosis is a disease characterized by low bone mass and structural deterioration of bone tissue, leading to bone fragility and an increased risk of fractures of limbs and spine. There are several clinical risk factors that are connected either with primary (age, gender) or secondary (other diseases, taken drugs) form of osteoporosis. The drop in estrogen concentration in postmenopausal women is the main cause for the higher fracture risk in this group when comparing with men in the same age. Other diseases characterized by hypoestrogenism (such as anorexia nervosa) also decrease bone mineral density. The aim of the osteoporosis treatment is to prevent new fractures. Treatment should be considered in individuals subsequently shown to have a high fracture risk. Several medications are available for the prevention and treatment of osteoporosis. The hormone replacement therapy used for the treatment on menopausal symptoms have also an impact on low- fracture risk. However, it should not be considered as a first line treatment on osteoporosis. Calcium and vitamin D supply as well as exercise lower fracture risk and improve quality of live of postmenopausal women.